PEMBUATAN RAK PADA CV. AYUNA SILVER UNTUK MEMBANTU MENGATUR LETAK CETAKAN CINCIN - Dirgayusari, Ayu Manik; Andika, I Gede; Desnanjaya, I Gusti Made Ngurah; Hartawan, I Nyoman Buda; Nirwana, Ni Kadek Ayu; Wiradana, I Made Adi (PUAN INDONESIA, 2024)
The ring mold storage rack created is equipped with a ring mold search system as an alternative for the automatic ring mold search process. This system is built with several supporting components such as ESP32 microcontroller, Servo Motor, L9110 Motor Driver, DC Gearbox Motor, 16x2 LED. The result of this service activity is the creation of an automatic ring mold storage rack which is able to simplify and reduce the time of the ring mold searching process at CV. Ayuna Silver. The final results obtained from several testing processes carried out contained 3 invalid results from 10 system tests, this shows that the system has a system success percentage of up to 70%. The time needed to search for rubber molds before the automatic ring mold storage rack was around 20 minutes, after the automatic ring mold storage rack was installed using a mobile system, it was only take 0.20 minutes or 12 seconds.